Improvements in Behavioral Symptoms following Antibiotic Therapy in a 14-Year-Old Male with Autism - Ramirez, P. Lucas; Barnhill, Kelly; Gutierrez, Alan; Schutte, Claire; Hewitson, Laura (Case Reports in Psychiatry, 2013)
This case report describes the benefits of antibiotic and antifungal therapy on behavior in a child with autism undergoing treatment for encopresis. Over the course of treatment, the child exhibited a reduction in aberrant behaviors, increased gastrointestinal function, and improved quality of life.